2019
DOI: 10.1186/s12889-019-6660-1
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods exploratory study tackling smoking during pregnancy in an urban Aboriginal and Torres Strait Islander primary health care service

Abstract: BackgroundPregnancy can be a time of joy and a time of significant stress. For many Aboriginal and Torres Strait Islander (hereafter, respectfully, Indigenous) women, cigarette smoking, even during pregnancy, is a socially sanctioned behavioural response to stress. Indigenous women smoke during pregnancy at higher rates than their non-Indigenous counterparts.MethodsA mixed methods, exploratory study, undertaken in an urban, Indigenous primary health care service, tested the impact and acceptability of a smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…From this foundation, programs that recognize and support self-agency, foster supportive relationships at the family and community level, and facilitate non-judgmental access to the available resources and organizations to ameliorate the immediate impact of the social and structural determinants of health are likely to be effective, particularly when combined with smoking cessation support tailored to each individual's needs [4,8,20,24]. Underpinned by this understanding, a holistic multifaceted smoking cessation in pregnancy program, the Empowering Strong Families (ESF) 4077 program, was developed and implemented in an urban Aboriginal and Torres Strait Islander community in Brisbane, Australia [25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…From this foundation, programs that recognize and support self-agency, foster supportive relationships at the family and community level, and facilitate non-judgmental access to the available resources and organizations to ameliorate the immediate impact of the social and structural determinants of health are likely to be effective, particularly when combined with smoking cessation support tailored to each individual's needs [4,8,20,24]. Underpinned by this understanding, a holistic multifaceted smoking cessation in pregnancy program, the Empowering Strong Families (ESF) 4077 program, was developed and implemented in an urban Aboriginal and Torres Strait Islander community in Brisbane, Australia [25].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-one pregnant women and 16 significant others participated in ESF. The acceptability and impact of the ESF intervention were determined through a mixed methods, exploratory study reported in detail elsewhere [25]. Over one-third of pregnant women (36% (4/11)) had quit at the three-month assessment, with two remaining smoke free one month postpartum.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A family that encounters culturally competent professionals and goes on to develop a sense of trust and cultural safety may be more likely to engage with the range of support services offered (Askew et al 2019). Until mainstream health services prioritize First Nations culture in strategy and organizational processes (such as through the NSW Health Services Cultural Engagement Self-Assessment Tool), First Nations peoples will be "still waiting for trust" (Herring et al 2013) in the interface between child protection and healthcare systems.…”
Section: Cultural Safety To Reorient Power Imbalancesmentioning
confidence: 99%